Total phenolic, antioxidant, antimicrobial, activities and toxicity study of Gynotroches Axillaris Blume (Rhizophoraceae) - Abed, Salam Ahmed; Mohd Sirat, Hasnah; Bakhtiar, M. Taher (University of Mainz, 2013)
The antioxidant activity and the total phenolic content, as well as the influence of petroleum ether, chloroform and methanol extracts from the leaves of Gynotroches axillaris, on micro- organisms were studied. The total phenolic contents were evaluated by using Folin-Ciocalteu reagent and the obtained values ranged from 70.0 to 620 mg GAE/g. The efficiency of antiox- idation, which was identified through the scavenging of free radical DPPH, exhibited that the highest IC50 was in the methanolic extract (44.7 μg/mL) as compared to the standard ascorbic acid (25.83 μg/mL) and to standard BHT (17.2 μg/mL). In vitro antimicrobial activity of ex- tracts was tested against Gram-negative bacteria, Gram-positive bacteria and fungi. Methanol extract showed activity in the range (225-900 μg/mL) with both types, while petroleum ether and chloroform extracts were only active with Bacillus subtilis. The three extracts strongly inhibited all fungi with activity 225-450 μg/mL. The toxicity test against brine shrimps indi- cated that all extracts were non-toxic with LC50 value more than 1000 μg/mL. The finding of this study supports the safety of these extracts to be used in medical treatments.